A horse or a zebra? Unusual manifestations of common cutaneous infections in primary immunodeficiency pediatric patients - Ollech, Ayelet; Simon, Amos J; Lev, Atar; Stauber, Tali; Sherman, Gilad; Solomon, Michal; Barzilai, Aviv; Somech, Raz; Greenberger, Shoshana (Frontiers in Pediatrics, 2023)
Background Patients with primary immunodeficiency disorders (PIDs) often suffer from recurrent infections because of their inappropriate immune response to both common and less common pathogens. These patients may present with unique and severe cutaneous infectious manifestations that are not common in healthy individuals and may be more challenging to diagnose and treat. Objective To describe a cohort of patients with PIDs with atypical presentations of skin infections, who posed a diagnostic and/or therapeutic challenge. Methods This is a retrospective study of pediatric patients with PID with atypical presentations of infections, who were treated at the immunodeficiency specialty clinic and the pediatric dermatology clinic at the Sheba Medical Center between September 2012 and August 2022. Epidemiologic data, PID diagnosis, infectious etiology, presentation, course, and treatment were recorded. Results Eight children with a diagnosis of PID were included, five of whom were boys. The average age at PID diagnosis was 1.7 (±SD 3.2) years. The average age of cutaneous infection was 6.9 (±SD 5.9) years. Three patients were born to consanguineous parents. The PIDs included the following: common variable immunodeficiency, severe combined immunodeficiency, DOCK8 deficiency, ataxia telangiectasia, CARD11 deficiency, MALT1 deficiency, chronic granulomatous disease, and a combined cellular and humoral immunodeficiency syndrome of unknown etiology. The infections included the following: ulcerative-hemorrhagic varicella-zoster virus (two cases) atypical fungal and bacterial infections, resistant Norwegian scabies, giant perianal verrucae (two cases), and diffuse molluscum contagiosum. Conclusions In this case series, we present unusual manifestations of infectious skin diseases in pediatric patients with PID. In some of the cases, recognition of the infectious process prompted life-saving treatment. Increasing familiarity with these dermatological manifestations, as well as keeping a high index of suspicion, is important to enabling early diagnosis of cutaneous infections in PIDs and initiation of prompt suitable treatment.